Massive Pleural Effusion in Tuberculosis Due to Systemic Lupus Erythematosus: A Case Report - Anthony Tjajaindra; Veronica Winda Soesanto; Anak Agung Made Sucipta (The International Journal of Medical Science and Health Research, 2025)
Introduction : Tuberculosis (TB) posed a significant risk for mortality and morbidity in autoimmune disorders like systemic lupus erythematosus (SLE). TB in SLE patients often manifests as extrapulmonary disease, affecting areas like the pleura, leading to pleuritis and effusion. This case report aims to assess a case of massive pleural effusion in tuberculosis patient due to co-existing SLE. Case Description : We present the case of a 17 y.o. girl who experienced progressive shortness of breath, worsening one day prior to her admission to the Emergency Department of Wangaya Regional General Hospital. Examination indicated a massive pleural effusion. Pleural drainage was performed the following day, yielding a total of 2,800 mL of pleural fluid. Further examination revealed symptoms of SLE, strengthen by family history. A positive antinuclear antibody (ANA) test confirmed the diagnosis of SLE. Patient then given pulse intravenous methylprednisolone at dose of 600 mg once a day for three days and antituberculosis Fixed-Dose Combination therapy. After the effusion resolved, patient had outpatient treatment and control periodically.  Conclusion : The increased risk of tuberculosis in SLE individual linked to immunological abnormalities in SLE, which hampers the body’s ability to control TB infection. Suspecting of SLE in patients with massive pleural effusion can lead to prompt treatment.